A mutual inductance sensor for cryogenic radial displacement measurement. (April 2021) - Guan, Xiang; Zou, Yincai; Shang, Jin; Bian, Xing; Wu, Jihao; Li, Qing
Highlights: A type of mutual inductance sensor based on the PCB technology is proposed forcryogenic radial displacement measurement. A simple and flexible experimental setup is designed. The results at low temperature and room temperature are compared, and the feasibility of the scheme is analyzed and verified. Abstract: In this paper, a type of mutual inductance sensor based on the PCB technology is proposed for cryogenic radial displacement measurement. Firstly, the feasibility of the scheme is analyzed from the aspects of the low temperature usability of materials and components, and the temperature sensitivity of the sensor. Then the experiments at low temperature (77 K) and room temperature are carried out with a simple and effective setup. The experimental results show that the sensitivity has no obvious change from room temperature to low temperature, and the linearity remains at a good level. However, the standard deviation and repeatability of the measurement are affected by external factors. Generally speaking, this paper verifies the feasibility of applying this sensor to micro displacement measurement at low temperature, which lays a foundation for the development of more mature displacement sensor for HTS bearing.